The AI Transparency Imperative: Should Patients Be Told When Artificial Intelligence is Used in Their Care? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The integration of Artificial Intelligence AI into clinical practice is rapidly transforming healthcare, offering unprecedented capabilities in diagnostics, ...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Clinical Decision Support; Medical Ethics